Development and Validation of the Purity Orientation–Pollution Avoidance Scale: A Study With Japanese Sample - Kitamura, Hideya; Matsuo, Akiko (Frontiers in Psychology, 2021)
The Moral Foundations Theory (MFT) proposes that there are five moral foundations that work as the standard to make moral judgements. Among them, Purity foundation is a complex concept. It is considered to be a distinctive foundation compared to the other ones partly because it involves religious beliefs. The assumption underlying Purity foundation is Christian beliefs so that the MFT was developed and made prevalent mostly in the Western cultures. However, because of that assumption, cultural differences in perceiving Purity foundation should be observed with a non-Western sample, such as Japan. It would be important to discuss and clarify Japanese unique aspect of their orientation toward the pure and impure. We constituted a scale to measure people’s tendency towards Purity Orientation-Pollution Avoidance (POPA), based on the purity/sanctity subscale of the Moral Foundations Theory. For validation, we administered several scales along with POPA. In study 1, we developed the scale and measured the relationship between the degree of one’s POPA, disgust, and animism. We identified four factors as POPA subscales. In study 2, we investigated the test-retest reliability of POPA and conducted questionnaire surveys to measure attitudes toward paranormal phenomena and the degree of concern for each of the moral foundations. The results showed the validity of the scale, based on the moderate correlations with other scales. The POPA can be a promising tool to better understand the phenomena involving purity foundation in the Japanese context.